On Naivety of T Cells in Inflammatory Bowel Disease: A Review. Issue 1 (January 2015) - Smids, Carolijn; Horjus Talabur Horje, Carmen S.; Wahab, Peter J.; Groenen, Marcel J. M.; Middendorp, Sabine; van Lochem, Ellen G.
Abstract : Abstract: Little is known about different phases of T-cell maturation in gut mucosa. Based on current knowledge about the migratory pathways of naive and memory T cells, it is believed that access to peripheral, nonlymphoid tissues is restricted to memory T cells. Surprisingly, there is increasing evidence of high numbers of naive T cells in the chronically inflamed gut tissue of patients with inflammatory bowel disease. This could partially be explained by new formation of ectopic lymphoid organs. Ongoing recruitment of naive T cells at inflammatory sites might play a role in the immunopathogenesis of inflammatory bowel disease. Abstract : Article first published online 29 September 2014.